Species of terrestrial gastropods (Gastropoda: Mollusca) in Phuong Hoang mountain, Phu Thuong commune, Vo Nhai district, Thai Nguyen province - Nguyễn Thanh, Bình; Hoàng Ngọc, Khắc; Hoàng Văn , Ngọc; Đỗ Công, Ba (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2021)
Study on species of terrestrial gastropods (Gastropoda: Mollusca) in Phuong Hoang mountain, Vo Nhai district, Thai Nguyen province was conducted from 12/2016 to 5/2017. A total of 48 species of 32 genera, 13 families were recorded from 30 quadrats plots. Of which, the most diversity Cyclophoridae family has 12 species, the next, the Camaenidae family has 8 species, Ariophantidae has 7 species, Pupinidae has 5 species, Achatinidae and Clausiliidae has 4 species, Chronidae has 2 species. The lowest has 6 families (Diplommatinidae, Enidae, Veronicellidae, Streptaxidae, Plectopylidae and Philomycidae has only one species. The most popular and abundant species is Diplommatina balansai robusta accounting for 15,99%, of the total species. Other species have low abundance (P% ≤ 10%). The species of terrestrial gastropods are distributed in areas with thick litter, the average density is 18,77 individuals/m2, average temperature from 200C - 280C, average humidity 67% - 88%. The richest species of snails (26 species, accounting for 97,92%) are found in limestone karst forest.